The genus Frankliniella (Thysanoptera: Thripidae) in Persea americana Mill. cv Hass on central highlands in Costa Rica - Rodríguez-Arrieta, Jesús Alexander (2023)
Introduction. Some species of thrips in the genus Frankliniella (Thysanoptera: Thripidae) are of quarantine importance in various crops in the Central American region. Meanwhile, several species of this genus have been reported as part of the visitor fauna and flowering plants, not only in plants with agricultural production. Objective. To record the species of Frankliniella associated with avocado trees and their cultivars weeds in the central region of Costa Rica and to present a key for the identification of these thrips. Materials and methods. Sampling was carried out every two months in three different zones in the central region of Costa Rica during the years 2019 to 2021. Thrips from avocado and weeds were collected by tapping branches and were prepared for viewing under a conventional light microscope and identified by their morphology. Results. Twenty-two species of Frankliniella were identified, eighteen of which were associated with weeds growing in the same cultivars, while five species were directly associated with the foliage and flowers of the avocado tree. Conclusion. In the central region of Costa Rica, three species of the genus Frankliniella were found on the avocado tree during flowering stage: F. alonso, F. doris and F. nita, one species on the foliage: F. sandovalensis, and one species on both foliage and flowering: F. cephalica.